DESCRIPTIVE STUDY OF TEMPORAL AND KINEMATIC GAIT PARAMETERS IN YOUNG FEMALE ADULTS (Fiep Bulletin - online, 2012)
The human body is a system capable of performing many movements, walking in is one of the most common performed skills. It is very important to undertand the normal walking pattern adopted by the young and healthy, in order to be able to study the changes resulting from pathological conditions. Therefore, this study aims to make a descriptive analysis of kinematic and temporal parameters of one step thoughout a walking condition. The variables analyzed were the joint angles of the lower limb, duration and step length of young female adults. In addition, the study compares whether there are differences in the walking pattern among three repetition trials of the step gesture. Ten women aged between 18 and 23 years participated in the study which consists of recording the step biomechanical variables while walking. No significant differences were found between the three step trials analyzed. The values ??found for the stride duration and length were 0.73 s. and 125.86 cm respectively. Concerning the step duration and length were found 0.39 s. and 35.93 cm. The mean values ??for the hip were 166° and 188°; for the knee 177° and 151° and for the ankle angle 120° and 123° in the stance phase and in the impulse phase, respectively.
Keywords: kinematics; human gait; angle of gait.